The effect of hospital-to-home transitional care using a digital messaging application on the health outcomes of patients undergoing CABG and their family caregivers: a randomized controlled trial study protocol - Maleki, Maryam; Mardani, Abbas; Iloonkashkooli, Raziyeh; Khachian, Alice; Glarcher, Manela; Vaismoradi, Mojtaba (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Given the increasing trend of care transition from healthcare settings to patients’ own home, patients and their family caregivers should take more responsibilities for care at own home. This study is going to investigate the effect of a transitional care program from hospital to own home using a digital messaging application on patients’ undergoing coronary artery bypass graft surgery (CABG) and their family caregivers’ health outcomes. Methods: A parallel randomized controlled trial study will be conducted in a hospital in a metropolis located in southwestern Iran. Sampling will be performed sequentially and the eligible dyad of patients and family caregivers will be randomly assigned to intervention and control groups. The intervention group will receive a transitional care program for 8 weeks using the WhatsApp on the mobile phone based on the person-centered care approach, but the control group will receive routine care for patient’s transition. Data collection will be conducted at baseline, immediately after the intervention, and two months after the intervention using demographic questionnaire, Cardiac Self-Efficacy Scale (CSES), MacNew Heart Disease Health-Related Quality of Life questionnaire (MNHD- Q), Cardiac Symptom Scale (CSS), Morisky Medication Adherence Scale, and Caregiver Burden Scale (CBS). Repeated ANOVA test will be used for data analysis. Conclusions: The results of this study will allow evaluating the effectiveness of an innovative transitional care program to patients’ own home using a digital messaging application. If the transitional program is shown feasible and effective it can be incorporated into existing care programs and stimulate further studies on the use of digital solutions for improving the continuity of care in own home.